2021
DOI: 10.3389/fonc.2021.650173
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulated LINC01667 Expression Is Correlated With Poor Prognosis in Hepatocellular Carcinoma

Abstract: The development of hepatocellular carcinoma (HCC) is a complex pathological process. Long intergenic non–protein-coding RNA 1667 (LINC01667, also known as MGC38584) plays an oncogenic role in several human cancers; however, its functional role in HCC tumorigenesis remains unknown. Here, we first evaluated the gene expression levels of LINC01667 in HCC using data from The Cancer Genome Atlas and Gene Expression Profiling Interactive Analysis (GEPIA) databases. We then elucidated the association between LINC0166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Secondly, there are three genes shared among the three groups of cancer patients but not with the group of healthy individuals, namely BAGE2, HAVCR1P1, and LINC01667. Numerous studies have reported the correlation of the abnormal expression of BAGE2 [ 22 , 23 ] and LINC01667 [ 24 ] with carcinogenesis of multiple types of cancers. Therefore, these genes could be potential biomarkers to discriminate healthy individuals from cancer patients in general.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, there are three genes shared among the three groups of cancer patients but not with the group of healthy individuals, namely BAGE2, HAVCR1P1, and LINC01667. Numerous studies have reported the correlation of the abnormal expression of BAGE2 [ 22 , 23 ] and LINC01667 [ 24 ] with carcinogenesis of multiple types of cancers. Therefore, these genes could be potential biomarkers to discriminate healthy individuals from cancer patients in general.…”
Section: Resultsmentioning
confidence: 99%
“…Human HCC cells HepG2, HUH7, HCC-LM3 and control cells L02 were obtained from the Type Culture Collection Cell Bank. Methods for cell culture have been outlined in prior research ( Yu et al, 2021 ; Zhang et al, 2021 ). Rabbit polyclonal anti-TUBG1 antibody was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, the assignment of a certain histopathological grade based on morphological features alone can be subjective and prone to inter-observer variability [6]. In order to enhance the predictive power of pathological evaluations, molecular biomarkers can be used to supplement the morphological examination of tumor tissues as prognostic indicators [7][8][9].…”
Section: Introductionmentioning
confidence: 99%